A new approach to peri-urban area land use efficiency identification using multi-source datasets: A case study in 36 Chinese metropolitan areas. (January 2023) - He, Tingting; Lu, Youpeng; Yue, Wenze; Xiao, Wu; Shen, Xuehan; Shan, Zhuoran
Abstract: Land use efficiency (LUE) is considered a significant yardstick for guiding the practice toward sustainable urban development for metropolitan areas. However, existing evaluation methods on LUE ignore the urban function carrying capacity of the urban construction land. This study proposes a theoretical approach for measuring LUE from a vacancy-and-utilization perspective. Accordingly, the land use efficiency index (LUEI) measurement is built up by incorporating nighttime light intensity, population density, and facility density of built-up land. Furthermore, the spatial pattern of the peri-urban areas' LUEI of 36 metropolitan areas in China is investigated. There are three significant findings. First, the LUEIs of the peri-urban area in eastern and western areas are 0.102 and 0.116, respectively, which are almost twice higher than that of the central area, which is only 0.067. Second, the balance between the contributions of LUEI's indicators is conducive to promoting LUE, indicating a bucket effect for achieving high LUE. Third, the average LUEI of county units with fewer facilities is 1.27 and 2.65 times lower than county units with less population and human activities. This new method not only provides a practical way to monitor LUE but would also be an essential basis for land use management. Highlights: A new method for evaluating land use efficiency (LUE) is proposed. The new method is proven applicable in 36 metropolitan areas in China. A buckets effect for LUE indicators exists for achieving high LUE. An organized urban function spatial layout is conducive to LUE.